Imagem corporal e auto-estima em adolescentes do sexo feminino: considerações sobre um programa misto de intervenção - Maria Tereza Cordeiro Beling (2012)
Objective: to verify the effects and limitations of a multifocal intervention program focused in monitoring adolescent girls body image and self-esteem. Methods and procedures: the research was conducted with three groups, each one consisting of adolescents enrolled in the first high school year at public schools in Belo Horizonte/MG. The selection of institutions was done for convenience and at the same educational district. Each school was named under the number of received interventions: All Schools (1, 2 and 3) received a standard treatment intervention in Nutrition and Health (7 modules, 60 minutes each, fortnightly); Schools 2 and 3 received intervention in Psychology (7 additional modules of 60 minutes each) and the 3rd School was also included in intervention with physical activity (32 modules, 60 minutes each, 2 times per week). A trained and qualified team conducted activities in each major area, based on adaptations of the Canadian "EveryBODY is a Somebody" material, under the monitoring of the central researcher coordinator. The parameters and related outcomes were assessed by specific questionnaires before and after the 4 months follow-up. It was collected information about the number of meals per day and frequency ofconsumption of healthy and unhealthy foods, related to maintenance or weight gain, as estimates of changes in eating habits. The Rosenberg Scale 9adapted for Brazilian population) and The Body Figure Silhouettes (BFS) were applied to investigate, respectively, objective differences in self-esteem and body satisfaction among the groups. Weight, high and skin fold measurements were verified to check for potential changes in fat percentage and body shape in all groups; Schools n.2 and n.3 also underwent a complete anthropometric assessment, to verify changes provided by the physical activity on body weight and BMI. Analyses were performed with blinding statistical Professional and using the SPSS - Statistical Package for Social Sciences - 15.0, with the adequate tests and techniques. It was considered a 5% level of significance (p 0.05) in all tests. Results: The sample consisted of students from 13 to 18 years; 29 were from School n.1; 34 from School n.2 and 36 from School n.3. Most of them belonged to C/D Brazilians social classification. There were, at baseline, high rates of inactivity and body dissatisfaction (homogeneity was found in these and in the main interest outcomes). Comparing the combined strategies, there was a significant increase in the number of meals per day at ESC-3; moreover, no other item had significant effect on nutritional parameters and body satisfaction. No changes were detected in the self-esteem of the groups at the end of the study by objective assessments, but at the individual level, there were both, objective (School 3) and subjective (all schools) improvement. It was detected a dose-response effect: the highest exposure yielded the best benefits, which may be due to the methods aggregation of the formation of a sense of belonging to a group. Conclusion: It was proved the power of the three interventions arrangement to achieve significant beneficial results. It was attested the role of subjective evaluation in detecting improvements in constructs not assessed through objective testing, but yet related to establishing a good relationship with self body image. Some results may be limited by the assessment instruments, which deserve attention in intervention programs, as well as the proposed design and implementation methods. The work raised relevant issues new researches that address the body image theme and encouraged related reflections. It is suggested studies with greater duration and intensity and the measurement of other variables not yet investigated, incorporated the concept of body image, including a qualitative approach.